PENGARUH INFLASI, BI RATE, KURS DAN INDEKS DOW JONES INDUSTRIAL AVERAGE TERHADAP JAKARTA ISLAMIC INDEX (JII) - Muhammad Rasyid Ridha; Harmaini Harmaini (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
This research discusses the influence of inflation, BI Rate, Exchange rate (IDR/USD) and Dow Jones Industrial Average. The analysis method used is multiple linear regression model with α = 5%. With EViews 9.0 applications. The results of this research show that inflation, BI Rate, Foreign Exchange and Dow Jones Industrial Average simultaneously had significant influence towards on the Jakarta Islamic Index (JII). Meanwhile, partially Inflation had positive and significant influence towards on the JII. BI Rate partially had negative and significant influence towards on the JII. But Exchange rate (IDR/USD) partially do not influence on the JII and Dow Jones partially had positive and significant influence towards on the JII.